Customer Satisfaction at Alfamart Raya Sukodono: a Study on Product Quality and Service Excellence - Listiyana Listiyana (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
This study aims to determine the service quality, customer loyalty, and price and product quality of Alfamart Raya Sukodono. This study used a qualitative approach with a descriptive research type. The data collection techniques used in this study were interviews and observations. The results of this study are Friendly and responsive service quality provided by Alfamart Raya Sukodono is an important factor in influencing customer loyalty. Good service creates customer trust and comfort, motivating them to remain loyal and shop again at Alfamart Raya Sukodono. High customer loyalty at Alfamart Raya Sukodono results from a combination of several factors such as friendly and responsive service, attractive loyalty programs, and promotional activities. involving customers. then also Alfamart Raya Sukodono managed to offer its customers affordable prices and good product quality. The emphasis on competitive prices and adequate quality attracts customers who are looking for the best value in their shopping experience. By providing quality products at competitive prices, Alfamart Raya Sukodono maintains customer satisfaction and strengthens long-term relationships with them.